Pengaruh Peran Pemediasi Manajemen Laba dalam Hubungan antara Ukuran Perusahaan terhadap Kinerja Perusahaan dengan Mekanisme Corporate Governance sebagai Variabel Pemoderasi - Reza Fahlevi Lubis (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze and obtain empirical evidence regarding the influence of the Mediating Role of Earnings Management in the Relationship between Firm Size and Firm Performance with Corporate Governance Mechanisms as Moderating Variables. The sample in this study was BUMN based on purposive sampling in the 2016-2019 period. The research method used is descriptive quantitative method. The analytical technique used in this research is regression analysis using the WarpPLS 8.0 program. The results of the study indicate that the size of the company does not have a significant effect. Earnings Management can mediate the relationship between company size and company performance and The The Corporate Governance mechanism can be a moderator.